2017
DOI: 10.1634/theoncologist.2016-0277
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care Matters: Palliative Cancer Care Results in Better Care and Lower Costs

Abstract: This article reviews the current state of end‐of‐life care, analyzes the clinical and financial impact of palliative care, and proposes areas of future research and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 107 publications
0
61
0
2
Order By: Relevance
“…There is a critical need to prepare family carers for the complex role they face and to focus on ways to temper the burden of caregiving (Ferrell & Wittenberg, 2017). There is also a need for palliative care delivery models that benefit both caregivers and patients (Dalal & Bruera, 2017;Kavalieratos et al, 2016). By identifying and interpreting family nursing practice that addresses complex family needs, concerns, and distress, family members´ experiences of advanced cancer can be considered in the context of the family situation (IFNA, 2017;Wright & Bell, 2009;Wright & Leahey, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is a critical need to prepare family carers for the complex role they face and to focus on ways to temper the burden of caregiving (Ferrell & Wittenberg, 2017). There is also a need for palliative care delivery models that benefit both caregivers and patients (Dalal & Bruera, 2017;Kavalieratos et al, 2016). By identifying and interpreting family nursing practice that addresses complex family needs, concerns, and distress, family members´ experiences of advanced cancer can be considered in the context of the family situation (IFNA, 2017;Wright & Bell, 2009;Wright & Leahey, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that hospital-based PC services increased satisfaction of patients and families [45], improved QoL [46], reduced ICU length of stay [47], and decreased costs [48,49]. In a very recent review, the authors have underlined the advantages of a PC-oriented approach in improving patient's outcomes, including symptom burden, QoL, and EoL outcomes, all achieved with lower associated costs [50].…”
Section: What Role For Inhospital Palliative Care?mentioning
confidence: 99%
“…In a recent review Dalal and Bruera have reported that the magnitude of hospital cost savings with PC involvement ranged from 9 to 32% and these savings were higher when PC team was involved earlier (within two days from patient's admission) [50]. Two recent studies [62,63]…”
Section: Which Is the Impact Of Inhospital Palliative Care Services Omentioning
confidence: 99%
“…Additionally, the Patient Protection and Affordable Care Act, often called 'Obamacare' (statute 42 U.S.C.A § 300gg-8 under PPACA Section 2709), mandates that insurance companies must cover routine care costs for trial participants. While terminal lung cancer patients have increased access to medications, evidence suggests that end of life treatment is associated with worse quality-of-life (Dalal andBruera 2017, Zhang et al 2009), and that many clinical trials and experimental treatment options fail to extend life.…”
Section: Introductionmentioning
confidence: 99%